Deuterium trapping and release in JET ITER-like wall divertor tiles. (1st February 2016) - Likonen, J; Heinola, K; De Backer, A; Koivuranta, S; Hakola, A; Ayres, C F; Baron-Wiechec, A; Coad, P; Matthews, G F; Mayer, M; Widdowson, A
Abstract: A selected set of samples from JET-ILW divertor tiles exposed in 2011–2012 has been analysed using thermal desorption spectrometry (TDS). The highest amount of deuterium was found on the regions with the thickest deposited layers, i.e. on the horizontal (apron) part and on the top part of Tile 1, which resides deep in the scrape-off layer. Outer divertor Tiles 6, 7 and 8 had nearly an order of magnitude less deuterium. The co-deposited layers on the JET tiles and the W coatings contain C, O and Ni impurities which may change the desorption properties. The D2 signals in the TDS spectra were convoluted and the positions of the peaks were compared with the Be and C amounts but no correlations between them were found. The remaining fractions of D in the analysed samples at ITER baking temperature 350 °C are rather high implying that co-deposited films may be difficult to be de-tritiated.